2012
DOI: 10.5829/idosi.ije.2013.26.12c.06
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Various Parameters on Out-of-phase Thermo-mechanical Fatigue Lifetime of A356.0 Cast Aluminum Alloy

Abstract: In this paper, the effect of various parameters on the out-of-phase thermo-mechanical fatigue (OP-TMF) lifetime of the A356.0 cast aluminum alloy is investigated. Studied parameters include the maximum temperature, the dwell time, and the thermo-mechanical loading factor. OP-TMF tests are conducted considering realistic running conditions of diesel engine cylinder heads. The maximum temperature varies between 200 to 275°C and the thermo-mechanical loading factor, which is the ratio of the mechanical strain to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…From another perspective, the evolution of AI for optimization tasks [ 12 ] and the interpretation of complex models [ 39 , 40 ] has transformed the landscape across all fields of engineering science. The switchgear manufacturing industry is no exception and aligns with this trend.…”
Section: Resultsmentioning
confidence: 99%
“…From another perspective, the evolution of AI for optimization tasks [ 12 ] and the interpretation of complex models [ 39 , 40 ] has transformed the landscape across all fields of engineering science. The switchgear manufacturing industry is no exception and aligns with this trend.…”
Section: Resultsmentioning
confidence: 99%
“…First, the mechanical behavior of metals and alloys will be discussed, with a focus on aluminum alloys in the literature. Azadi et al (5) investigated how the dwell time, thermomechanical loading factor, and maximum temperature affected the thermomechanical fatigue behavior of aluminum alloys. Furthermore, research efforts have expanded to investigate the effects of various aging heat treatments on the hardness of aluminum alloy (6).…”
Section: Introductionmentioning
confidence: 99%
“…In connection with this, several researchers have conducted many studies on the fatigue behavior of AA5052 aluminum alloy. Azadi et al [11] investigated the effects of various parameters (maximum temperature, dwell time, thermo-mechanical loading factor) on the out-ofphase thermo-mechanical fatigue lifetime of the A356.0 casting aluminum alloy. They found that the maximum temperature and thermo-mechanical loading factor had a more significant effect on the lifetime compared to the dwell time.…”
Section: Introductionmentioning
confidence: 99%